Efficacy and tolerability of Liraglutide in combination with other antidiabetic drugs in type 2 diabetes - Zenari, L. (Acta Biomedica Atenei Parmensis, 2012)
We present a collection case report performed in 29 inadequately controlled diabetic and obese outpatients. The aim of this study was to verify metabolic effects of liraglutide in combination with other antidiabetic drugs. Across this study, liraglutide effectively and rapidly improves glycemic control (both fasting glycemia and HbA1c), body weight and systolic blood pressure, thus promoting the achievement of therapeutic targets proposed by the American Diabetes Association and European Association for the study of Diabetes and reducing cardiovascular risk profile of diabetic patients.